THE INFLUENCE OF POTATO VARIETY PECULIARITIES ON TUBERS’ AND STORAGE QUALITIES - Barabolia, O. V.; Vakuliuk, D. S.; Prudkyi, T. A. (Scientific Progress & Innovations, 2021)
Potato is an important food crop all over the world and the source of some significant vitamins and minerals. However, as any other vegetable, potato has only some time before it starts spoiling and becoming dangerous to human health. The purpose of the study was to analyze the cultivation of Ukrainian bred potato varieties in the complex of their properties, on the basis of which optimal temperatures of keeping and potato storage quality as well as the analysis of tubers affected by diseases were distinguished. The studies were conducted in 2020–2021 on a private farm in the village of Suprunivka (Poltava region). The varieties of Ukrainian (Povin early-ripening, Slovianka mid-ripening) and Holland selection (Picasso late-ripening) were used for the research. After harvesting, the potatoes were kept in the storage facilities with active and passive ventilation for long-term preservation. The determining of storage quality and potato tubers’ affection with diseases at different periods of keeping was conducted by laboratory method. The studies of the temperature impact and ventilation duration on potato tubers wounds’ healing showed that wounds’ healing in Picasso variety was more intensive (on the 8th day completely) at the air temperature of 14–16 0С in the premises and the healing was the worst in Povin early-ripening variety (by 81–86 %). The analysis of potato tubers’ storage quality showed that the increase in the term of their keeping decreased the output of marketable products as a result of tubers’ affection with diseases and their germination. Picasso late-ripening variety had the best stored marketable products (up to 80.3 %), and Povin early-ripening variety had worse marketable products (up to 73.1 %). It has also been found that at long-term keeping, potato loses its cooking qualities, which testifies to the expediency of consuming Povin early-ripening potato variety first of all, then Slovianka mid-ripening and Picasso late-ripening varieties, as the tastiness of Povin potato variety is the best before storing and the worst after 4 months of its storage.